Clustering Technique On Students' Vocabulary Mastery - Nurhanna Harahap (BAHAS, 2018)
Abstract Clustering is making a visual map the students to think creativity. This research aims to determine whetherclustering technique affect students’ vocabulary mastery or not.The design used in this research was QuasiExperimental. The population in this research were all class VII Mts Al-Washliyah Tanjung Haloban 2018/2019 academic year consisting of 84 people. The research sample was taken using a saturated sample technique with the experimental method. Test was used as the instrument in this research. The test were pre-test and post-test.The mean of student learning outcomes using clustering technique is 78.36 with a standard deviation of 7.18 while those that do not use is 59.52 with a standard deviation of 14.86. from the difference of mean values from real level a is 0.05 indicates that students who get treatment clustering technique is better than those who don't get it. so that it can be seen that the use of clustering technique affect students' vocabulary mastery at Mts Al-Washliyah Tanjung Haloban Academic Year 2018/2019. Keyword :Vocabulary and Clustering technique